Aldoxime dehydratases: production, immobilization, and use in multistep processes - Martínková, Ludmila; Kotik, Michael; Kulik, Natalia; Křístková, Barbora; Šťastná, Katarína; Winkler, Margit (Applied microbiology and biotechnology, 2024)
The synthesis of nitriles is of utmost importance for preparative organic chemistry. The classical routes are often associated with disadvantages such as toxicity of the reagents and drastic conditions. The uses of enzymes like aldoxime dehydratases (Oxds) and hydroxynitrile lyases constitute attractive benign alternatives. In this review, we summarize the recent trends regarding Oxds. Thousands of oxd genes were sequenced but less than thirty Oxds were investigated on protein level. We give an overview of these Oxds, their sequence analysis, conditions required for their overexpression, and their purification and assays. We then focus on the use of Oxds especially in multistep reactions combining the chemical or chemoenzymatic synthesis of aldoximes from different starting materials with the enzymatic dehydration of aldoximes to nitriles, possibly followed by the hydration of nitriles to amides. Progress in Oxd immobilization is also highlighted. Based on data published mainly in the last 5 years, we evaluate the industrial prospects of these enzyme processes in comparison with some other innovations in nitrile synthesis. KEY POINTS: • Aldoxime dehydratases (Oxds) are promising for cyanide-free routes to nitriles • A comprehensive overview of wet-lab explored Oxds is provided • Recent trends include combining Oxds with other enzymes or chemical catalysts.
Keywords: Hydro-Lyases; oximy; dehydratasy; Multistep reaction; Biocatalyst; Nitriles; Immobilization; Oximes; enzymy imobilizované; nitrily; Enzymes, Immobilized; Aldoxime dehydratase; Nitrile synthesis